1999
DOI: 10.1111/j.1553-2712.1999.tb00112.x
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Effects of Hunger in an Emergency Department Patient Population

Abstract: Abstract. Objectives:Little is known about the prevalence and health effects of hunger among ED patients. The objectives of this study were to determine the prevalence of hunger among patients in a large urban ED and to examine whether it has adverse health effects. Methods: A survey about hunger, choices between buying food and buying medicine, and adverse health outcomes related to food adequacy over the preceding 12 months was administered to a convenience sample of adult non-critically ill ED patients from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 13 publications
5
46
1
Order By: Relevance
“…11 In studies of ED patients, those confronted with these trade-offs between food and medication believed that their choices caused illness, resulting in increased ED use and hospitalization. 10,12 Food insufficiency may adversely impact disease self-management and treatment adherence, leading to poorer overall disease control. 15 Indeed, homeless diabetics in Toronto reported that inadequate dietary choices were a principal barrier to disease management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 In studies of ED patients, those confronted with these trade-offs between food and medication believed that their choices caused illness, resulting in increased ED use and hospitalization. 10,12 Food insufficiency may adversely impact disease self-management and treatment adherence, leading to poorer overall disease control. 15 Indeed, homeless diabetics in Toronto reported that inadequate dietary choices were a principal barrier to disease management.…”
Section: Discussionmentioning
confidence: 99%
“…Competing demands for food are common among homeless individuals and may influence health care utilization patterns. [4][5][6] Homeless people who do not get enough food to eat may postpone or forego needed medical care until later stages of illness, [6][7][8][9] choose to buy food over medications, [10][11][12] or have difficulty managing health conditions and adhering to treatment plans. [13][14][15] In some cases, homeless people may use health services in order to get food.…”
Section: Introductionmentioning
confidence: 99%
“…The confidential interview lasted between 5 and 15 minutes, and included previously validated questions to assess the prevalence of food insecurity and hunger. 1,4,11 The survey also asked about respondent demographics, medical history, insurance status, medications taken, frequency of ED visits, ease of access to medical care, and perceptions of their health status. Further questions considered decision making between buying food and buying medicine, or choosing other nonfood items (i.e., clothes, shelter, cigarettes, alcohol) instead of purchasing prescribed medications.…”
Section: Methodsmentioning
confidence: 99%
“…When limited financial and other resources forced a choice between buying necessary prescription medications and buying food, almost 14% chose food and believed this choice had a detrimental effect on their health, resulting in frequent ED visits and hospitalizations. 11 However, this study included only those patients who spoke English and theoretically should have access to various community-wide social services that provide services in English. In addition, since our first study, many social services have undergone drastic budget cuts, including some directed toward newly arrived immigrants.…”
mentioning
confidence: 99%
“…37,47 Food insufficient individuals, people who skip meals or eat less than they feel they should because of money, choose less costly and less healthy diets, leading to more obesity and greater health care utilization. 48 Racism and discrimination affect health directly, in addition to effects on socioeconomic status, which also impacts health. 49,50 Minority populations are less likely to receive the same procedures for the same medical conditions as Whites.…”
Section: Our Model: Conceptual Frameworkmentioning
confidence: 99%